Convolutional Neural Network on Brain Concentration and Art of Reading the Qur'an (Mobile and Forensics, 2022)
In Islam there is a belief that reading the Qur'an can increase one's concentration power in doing something. Concentration can be influenced by several factors, to be able to identify or characterize individuals, it is necessary to measure brain wave activity. Brain waves are one of the biometric properties that can be used to identify individuals based on their physical. An electroencephalogram (EEG) can be used to measure and capture brain wave activity. To be able to naturally record brain wave activity requires constant and emergent brain activity. The activities needed are in the form of giving assignments to get the thinking process and concentration needed for the Basic Cognitive Test. The object of this research is the students of the University in Yogyakarta. EEG data recording was carried out in two stages, the first stage the respondents were given 10 minutes to work on the test questions without reading the Qur'an before working on the questions, the second stage the respondents were given 10 minutes to work on the test questions by reading the Qur'an before doing the work. about. When the respondent was working on the test, the researcher recorded the EEG signal using Neurosky Mindwave Mobile 2, so that the data in the form of brain signals was obtained. The data acquisition will undergo a preprocessing process in the form of a domain transformation signal using Fast Fourier Transform (FFT). Then enter the labeling process and after that the next process will be carried out the classification process using the CNN algorithm. The results of this study showed that 10 of 30 students' concentration levels experienced an increase, with an accuracy rate of 85% and a significant F test is 0.002